Socio-Demographic Determinants of Medication Compliance in Bipolar Disorder Patients in Lahore, Pakistan - Fatima, Mubeen; Umar, Ahmad; Shirwany, Abdul Sammad Ali Khan; Akhtar, Abdul Majeed; Gohar, Awais; Azhar, Syed Hanzila (Biological and Clinical Sciences Research Journal, 2025)
Medication non-compliance is a major challenge in the long-term management of bipolar disorder, contributing to relapse, hospitalization, and poor quality of life. Socio-demographic factors can significantly influence adherence behavior, yet data specific to the Pakistani population remain limited. Objectives: The study’s primary objective was to evaluate medication compliance in bipolar patients and identify the associated socio-demographic variables affecting medication compliance. Methodology: An analytical cross-sectional study was conducted at the teaching hospital in Lahore, Punjab, which specializes in mental health. A questionnaire based on the Self-Efficacy for Appropriate Medication Use Scale (SEAMS) was utilized, with a sample size of 296 patients aged 18 and above. Statistical analysis was performed using R Studio software. Results: The analysis revealed a median SEAMS score of 19 (IQR = 18, 22). Males demonstrated slightly higher adherence than females (median SEAMS score of 20 vs. 19, respectively). Unmarried individuals exhibited better adherence (median = 21) than married participants (median = 19). Students reported the highest compliance (median = 22), while unemployed individuals had the lowest (median = 18). Significant differences in SEAMS scores were observed across employment and education levels. The robust gamma regression analysis confirmed that uneducated participants (exp(β) = 0.836, p < 0.001) and unemployed individuals (exp(β) = 0.980, p = 0.219) exhibited lower adherence. Additionally, those aged 30-44 and 45-59 showed significantly higher adherence (exp(β) = 1.048, p = 0.014 and exp(β) = 1.050, p = 0.026, respectively). Conclusion: The study highlights the significant influence of sociodemographic factors, particularly employment status and education level, on medication compliance. While gender and age also contribute, the findings suggest that targeted interventions aimed at addressing disparities in employment and education could improve medication adherence in patients with bipolar disorder.